Pharmacokinetic Profile of Curcumin and Nanocurcumin in Plasma, Ovary, and Other Tissues - Arozal, Wawaimuli; Ramadanty, Wenny Trias; Louisa, Melva; Satyana, Regina Puspa Utami; Hartono, Gaviota; Fatrin, Serlie; Purbadi, Sigit; Estuningtyas, Ari; Instiaty, Instiaty (Drug Research, 2019)
Background Curcumin is a natural diphenolic compound that is currently being investigated for various cancers, including ovarian cancer. Clinical application of curcumin has been limited due to its low solubility and bioavailability and rapid metabolism and degradation at physiological pH. Particle size is one factor that can affect the absorption process, which thus increases compound solubility and transport across the membrane. This study was conducted to determine the effects of modifying the particle size of curcumin on its pharmacokinetic parameters in blood and other organs.Methods Female Sprague Dawley rats were administered a single oral dose of 500 mg/kg curcumin or nanocurcumin. Blood samples were collected at 10, 15, 30, 45, 75, and 120 min, and ovaries, livers, kidneys, and colons were collected at 180 min. The levels of curcumin in plasma and organs were determined using UPLC-MS/MS, and the pharmacokinetic parameters were evaluated.Results Curcumin levels were detectable and measurable in plasma and organs of rats that were administered curcumin or nanocurcumin. Overall, no statistically significant differences were found in pharmacokinetic parameters between curcumin and nanocurcumin groups in both plasma and organs, except for ovaries. The curcumin levels in plasma, liver, kidney, and colon in the curcumin group were higher than those in the nanocurcumin group. However, curcumin concentrations in ovaries in the nanocurcumin group were 3.6 times higher than those in the curcumin group.Conclusion Particle size reduction of curcumin did not increase the concentration of curcumin in the plasma but increased its distribution in the ovaries.
Keywords: curcumin; nanoparticle; pharmacokinetic; ovary